Engagement in the past and in the present. Change in the way of preparing for marriage - Ładyżyński, Andrzej (Karkonoska Państwowa Szkoła Wyższa, 2011)
19th and 20 th century morals guides written for persons in diverse life situations constitute a basis for the article presented. The decoding of the contemporary and historic meanings of engagement was attempted from that perspective. Pre-marital relationships would always constitute an important stage of transition. Their arranging initially depended on the senior members of families, with the feelings and opinions of the engaged hardly ever taken into account. Changes in the forms of establishing and functioning of relationships preceding marriage took place in the second half of the 20 century.
Keywords: engagement; family; changes; guides